2014
DOI: 10.1186/1472-6920-14-184
|View full text |Cite
|
Sign up to set email alerts
|

Family physicians’ professional identity formation: a study protocol to explore impression management processes in institutional academic contexts

Abstract: BackgroundDespite significant differences in terms of medical training and health care context, the phenomenon of medical students’ declining interest in family medicine has been well documented in North America and in many other developed countries as well. As part of a research program on family physicians’ professional identity formation initiated in 2007, the purpose of the present investigation is to examine in-depth how family physicians construct their professional image in academic contexts; in other w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
0
13
0
4
Order By: Relevance
“…Among the 72 articles included in the review (see Appendix S1, online, for a full list), 10 papers reported findings from four overarching studies. These included three papers by Rodr ıguez et al, [15][16][17] one paper by L opez-Roig et al, 18 two papers by Van Hoof et al, 19,20 one paper by Maggio 21 and one by Maggio et al, 22 and two papers by Preston et al 23,24 The articles reviewed utilised a CSR approach for a diverse range of topics (Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 72 articles included in the review (see Appendix S1, online, for a full list), 10 papers reported findings from four overarching studies. These included three papers by Rodr ıguez et al, [15][16][17] one paper by L opez-Roig et al, 18 two papers by Van Hoof et al, 19,20 one paper by Maggio 21 and one by Maggio et al, 22 and two papers by Preston et al 23,24 The articles reviewed utilised a CSR approach for a diverse range of topics (Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
“…Imagens constituem instrumentos utilizados pelo homem, sendo o elemento cognitivo básico do pensamento capaz de influenciar e direcionar o pensamento (DE TONI;SCHULER, 2007;DE TONI, 2008). A partir das imagens, é possível determinar quais informações receberão mais atenção ou não, e como as pessoas expressam o modo como veem ou representam um objeto (RODRÍGUEZ et al, 2014).…”
Section: Imagem E Suas Dimensõesunclassified
“…Professional identity is viewed as an ongoing process that first encompasses the 'sense of self', created through social interactions with others, including other professionals and service users (Rodríguez et al 2014). These interactions shape our identity and make us behave in a way that is considered acceptable by our peers and others.…”
Section: Professional Identitymentioning
confidence: 99%